Principles and Contents Of Developing Patriotic Dignity In Students - Yusupovich, Mirzakarimov Xudaberdi (Indonesian Journal Publisher, 2024)
This article expresses the principles of education and training in development, the patriotic dignity of students and its importance in the process of education.